Pengetahuan Kepatuhan Penggunaan APD Pada Pekerja Home Industry Cetakan Paving Sidoarjo - Naufal Ilham Saputra; Muslikha Nourma Rhomadhoni; Zidni Ilman Nafia; Ratna Ayu Ratriwardani (Cv. Utility Project Solution, 2023)
Knowledge of the use of Personal Protective Equipment (PPE) at work is a must for workers in carrying out work to maintain occupational health and safety. An unfavorable attitude towards the use of PPE may be caused by several other factors such as the level of knowledge that affects attitude change. The purpose of this study was to measure the effect of knowledge level on compliance with the use of Personal Protective Equipment (PPE) of paving mold workers Sidoarjo. The application used is IBM SPSS Statistics with the One Group Pretest-Posttest Design research method. Based on the results of the study, a significance value of 0.829 was obtained, the value is greater than α 0.05, meaning Ho is accepted and Ha is rejected. This means that there is no significant difference before and afterthe K3 promotion socialization. However, when viewed the average (mean) obtained by workers through the pretest and post-test has increased, namely at the pretest value of 88.57 to 90.00 at the post-test value. Although workers have good knowledge, workers do not applythe OHS culture because they feel uncomfortable, uncomfortable and feel used to the work environment.